2021
DOI: 10.1007/s10840-020-00932-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between superior vena cava ablation in addition to pulmonary vein isolation and standard pulmonary vein isolation in patients with paroxysmal atrial fibrillation with the cryoballoon technique

Abstract: Background Paroxysmal atrial fibrillation (PAF) can be triggered by non-pulmonary vein foci, like the superior vena cava (SVC). The latter is correlated with improved result in terms of freedom from atrial tachycardias (ATs), when electrical isolation of this vessel utilizing radiofrequency energy (RF) is achieved. Objectives Evaluate the clinical impact, in patients with PAF, of the SVC isolation (SVCi) in addition to ordinary pulmonary vein isolation (PV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 26 publications
0
17
1
Order By: Relevance
“…Recently, a retrospective study by a highly experienced CB center demonstrated both the feasibility as well as a lower AF/AT recurrence when performing SCVI using the CB in patients with paroxysmal AF. However, the incidence of PNP and sinus node impairment was increased [15]. For repeat procedures in patients with AF/AT recurrence after index PVI, there currently only exists one study which investigates the value of additional SVCI on top of PVI [12].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a retrospective study by a highly experienced CB center demonstrated both the feasibility as well as a lower AF/AT recurrence when performing SCVI using the CB in patients with paroxysmal AF. However, the incidence of PNP and sinus node impairment was increased [15]. For repeat procedures in patients with AF/AT recurrence after index PVI, there currently only exists one study which investigates the value of additional SVCI on top of PVI [12].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, patients with concealed non-PV triggers in the Asian population were most likely to be with SVC triggers and could benefit from empirical SVC isolation, which is in consistency with the results from other population. Additionally, unlike other non-PV triggers elimination, SVC isolation is a more commonly applied technique with exact endpoint, making the ablation results more replicable and reliable even when the non-PV triggers in uninducible., and superior vena cava isolation is proved to be safe and feasible ( 31 , 32 ). Our study demonstrated that empirical SVC isolation was the only independent predictor of recurrence after the second ablation of AF, suggesting that empirical SVC isolation improved the outcome of re-ablation in patients with all PVs isolated.…”
Section: Discussionmentioning
confidence: 99%
“…Cryoballoon has also been used to achieve SVCI and has improved freedom from AT in PAF subjects. (82) An empirical approach to SVCI has been investigated in a prospective, randomized study (83), which found no significant differences in maintenance of sinus rhythm without antiarrhythmic drugs . The same conclusion was derived from a meta-analysis by Sharma et al (84)including a total of 526 subjects, in which no difference in AF recurrence when SVCI was added to PVI across all types of AF.…”
Section: Superior Vena Cava Isolation (Svci)mentioning
confidence: 99%